Preliminary Study on Functional Groups Characteristics of Asphalt Containing Rice Husk Silica - Sembiring, Simon (Journal of Technomaterial Physics, 2019)
In this research, asphalt composite was produced by combining asphalt and rice husk silica. The ratio of asphalt and silica were 1:1.5; 1:1.7; and 1:1.9 respectively and calcined at temperature of 150 oC. Functional group characteristics of asphalt composites were examined by FTIR and XRD. The FTIR and XRD studies revealed that the main Functional groups are Si-O-Si, C-H, and structure amorph of silica.